IMAGES ON THE PLATES OF TAGAR KURGANS FENCES (TEPSEY ARCHAELOGICAL COMPLEX) - O. S. Sovetova; O. O. Shishkina (Вестник Кемеровского государственного университета, 2014)
The paper analyzes the petroglyphs on the rocks of Tagar mounds (kurgans) under the mountain Tepsey on the Yenisei, which represent a separate group of pictorial sources on the history of Southern Siberia. The earliest petroglyphs belong to thePodgornovo stage of the Tagar culture, the latest – to the ethnographic time. The most representative and varied petroglyphs belong to the Tagar culture. Petroglyphic images are quite different: anthropomorphic and zoomorphic images, abstract figures, tamgas etc. The petroglyphs show various techniques. Analysis of these images discovers the new sides of world outlook of their creators and gives the whole picture about thr particular time.